A study on deployment of resources for Selangor peat fires of 1998 - Kamaruzzaman, A Zulhany (2000)
This study is concerned with deployment of resources during the peat fires of 1998 in Selangor namely in Banting (32 days), Sepang-KLIA (7 days), Klang Selatan (7 days) and Sabak Bernam (17 days). The first part of the study deals with equipment used and number of personnel involved, while the second part deals with psychological preparedness of Bomba personnel in handling the peat fires. Klang Selatan deployed l l personnel /day or 13 ha/person; followed by Banting 6.43 personnel/day or 5 ha/person; Sepang-KLIA 5.71 personnel/day or 1 ha/person and Sabak Bernam 3.24 personnel/day or 8 ha/person. There were 21 types of equipment used with descending order of usage with Klang Selatan 313, Sepang-KLIA 279, Banting 209 and Sabak Bernam 165 (66 tents). Cost per personnel per area is RM 100l.30 for Sepang-KLIA and Banting, RM 1192.7 for Sabak Bemam and RM 319.5 for Klang Selatan. In the second part of the study, the psychological strength of Selangor Bomba personnel was assessed, using Ashken's (1993) questionnaires. The scoring for respective components in descending order are imager use, confidence, self talk use, arousal control, physical condition, attention control, commitment and physical arousal are 3.458, 3.272, 3.13,3.005,2.811,2.59,2.57 and 2.237, respectively. The total score of 23.071 is two points less than "you made the cut". The average performance of Bomba personnel for Peninsular Malaysia is 25.7. The respondents do not believe in drills for enhancing their performance. They were also offended by one question on drinking habits. Lesson learnt from the peat fires is use of a unified command system during crisis has to be enhanced. Lesson learnt when adopting questionnaires from other countries is to understand the cultural differences before adapting these questions for Malaysian scenano.